Protein Engineering of a Pyridoxal-5′-Phosphate-Dependent l-Aspartate-α-Decarboxylase from Tribolium castaneum for β-Alanine Production - Xin-Jun Yu; Chang-Yi Huang; Xiao-Dan Xu; Hong Chen; Miao-Jie Liang; Zhe-Xian Xu; Hui-Xia Xu; Zhao Wang (Molecules, 2020)
In the present study, a pyridoxal-5′-phosphate (PLP)-dependent L-aspartate-α-decarboxylase from Tribolium castaneum (TcPanD) was selected for protein engineering to efficiently produce β-alanine. A mutant TcPanD-R98H/K305S with a 2.45-fold higher activity than the wide type was selected through error-prone PCR, site-saturation mutagenesis, and 96-well plate screening technologies. The characterization of purified enzyme TcPanD-R98H/K305S showed that the optimal cofactor PLP concentration, temperature, and pH were 0.04% (m/v), 50 °C, and 7.0, respectively. The 1mM of Na+, Ni2+, Co2+, K+, and Ca2+ stimulated the activity of TcPanD-R98H/K305S, while only 5 mM of Ni2+ and Na+ could increase its activity. The kinetic analysis indicated that TcPanD-R98H/K305S had a higher substrate affinity and enzymatic reaction rate than the wild enzyme. A total of 267 g/L substrate l-aspartic acid was consumed and 170.5 g/L of β-alanine with a molar conversion of 95.5% was obtained under the optimal condition and 5-L reactor fermentation.